The Youth Labor Market Problem : Its Nature, Causes, and Consequences. - Freeman, Richard (National Bureau of Economic Research conference report., 1982)
This volume brings together a massive body of much-needed research information on a problem of crucial importance to labor economists, policy makers, and society in general: unemployment among the young. The thirteen studies detail the ambiguity and inadequacy of our present standard statistics as applied to youth employment, point out the error in many commonly accepted views, and show that many critically important aspects of this problem are not adequately understood. These studies also supply a significant amount of raw data, furnish a platform for further research and theoretical work in.